Melatonin-loaded self-healing hydrogel targets mitochondrial energy metabolism and promotes annulus fibrosus regeneration - Xiayu Hu; Xin Tian; Chunju Yang; Feng Ling; Hao Liu; Xuesong Zhu; Ming Pei; Huilin Yang; Tao Liu; Yong Xu; Fan He (Materials Today Bio, 2023)
Intervertebral disc (IVD) herniation is a major cause of chronic low back pain and disability. The current nucleus pulposus (NP) discectomy effectively relieves pain symptoms, but the annulus fibrosus (AF) defects are left unrepaired. Tissue engineering approaches show promise in treating AF injury and IVD degeneration; however, the presence of an inflammatory milieu at the injury site hinders the mitochondrial energy metabolism of AF cells, resulting in a lack of AF regeneration. In this study, we fabricated a dynamic self-healing hydrogel loaded with melatonin (an endocrine hormone well-known for its antioxidant and anti-inflammatory properties) and investigate whether melatonin-loaded hydrogel could promote AF defect repair by rescuing the matrix synthesis and energy metabolism of AF cells. The protective effects of melatonin on matrix components (e.g. type I and II collagen and aggrecan) in AF cells were observed in the presence of interleukin (IL)-1β. Additionally, melatonin was found to activate the nuclear factor erythroid 2-related factor signaling pathway, thereby safeguarding the mitochondrial function of AF cells from IL-1β, as evidenced by the increased level of adenosine triphosphate, mitochondrial membrane potential, and respiratory chain factor expression. The incorporation of melatonin into a self-healing hydrogel based on thiolated gelatin and β-cyclodextrin was proposed as a means of promoting AF regeneration. The successful implantation of melatonin-loaded hydrogel has been shown to facilitate in situ regeneration of AF tissue, thereby impeding IVD degeneration by preserving the hydration of nucleus pulposus in a rat box-cut IVD defect model. These findings offer compelling evidence that the development of a melatonin-loaded dynamic self-healing hydrogel can promote the mitochondrial functions of AF cells and represents a promising strategy for IVD regeneration.